The School of Site: Istanbul Walkabouts - Tümerdem , Nazlı (Journal of Public Pedagogies, 2019)
This article focuses on the potentialities of employing the practice of walking as a critical public pedagogy in the context of the transforming territories of northern Istanbul. It will initially give background information on the current processes of neoliberal urbanization taking place in northern Istanbul. It will then, based on the experience of the independent walking project Istanbul Walkabouts, discuss how walking can be used as a critical methodology outside and in academia to question hegemonic approaches to land, record the terra incognita areas of cities, and produce alternative modes of mapping. Ultimately, it will emphasize how performing critical walking in the precarious geographies of northern Istanbul with diverse publics can trigger experiential and place-based (un)learning, produce multiple epistemologies, and generate a community that is critically engaged with top-down approaches to urbanization.